The Washback Effects of Testing Practices on English Language Teaching - Nunun Nuki Erfiani (Department of English Language Education, UIN Sunan Ampel Surabaya, 2018)
Teachers often confused how they can get feedback from their students as one of supporting education components they need. Therefore, washback effects are important as the feedback. This essay studies the washback effects of testing practices on English language teaching. This essay covers three important parts which discuss washback effects. The first part tells the introduction which consists of background to the study, objectives of the study, and limitation of the problem. The second part clarifies English language teaching in Indonesia, English language teaching in Junior High Schools, testing practices on English language teaching, factors influence testing practices, washback effects of testing practices, and areas affected by washback. The third part reviews research studies on washback effects to explore the washback effects of testing practices on English language teaching. The last part, conclusion, is consistent with the effects of washback of testing practices on English language teaching.